Design attributes of educational computer software for optimising girls' participation in educational game playing - Rich, Warren Charles (Curtin University, 2004)
Recent research on girls in science education in Australian primary schools indicates a participation rate lower than that of boys. This inequality could lead subsequently to reduced opportunities for girls entering the workforce in their adult years. Many studies have attempted to reveal why this situation has arisen and a variety of strategies for increasing girls' participation has been suggested. A relatively new strategy that does not appear frequently in the research literature is the use of educational computer game software. An important question arises: does the game software used in primary school science education reflect design attributes favoured by boys and, if so, do these attributes actively discourage girls' participation by making them feel uncomfortable or stressed? My case study was designed to identify design features of computer games that girls prefer so that these features can be included in educational computer game software designed for science education, as well as the other Key Learning Areas. Through interviews, surveys and observations my interpretive study obtained the opinions and views of over 200 children in two suburban Australian primary schools in which I work as a teacher-librarian. In this role I purchase educational computer games and organize special classes for students to play them. From my analysis of the data I make recommendations that reflect girls' preferred design attributes for educational computer games. I also generate a checklist of criteria from my interpretations that may result in the purchase of software that could not only enhance girls' participation and success in primary school science, the curriculum area of greatest personal interest to me, but also in other Key Learning Areas of primary education.\